Institutional Transformation and Readiness in Executive Education Development - Gavin Torinno Hardipura; Elfrida Viesta Napitupulu (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
Higher education institutions are increasingly required to reposition strategically in response to evolving market demands and financial constraints. Executive education has emerged as a key avenue for institutional diversification; however, many universities encounter challenges due to insufficient organizational readiness rather than lack of strategic intent. This study develops an institutional transformation and readiness framework to explain how universities prepare for executive education as a strategic initiative. Using an exploratory qualitative multi-perspective design, data were collected from 14 informants comprising institutional leaders and industry stakeholders through in-depth interviews and analyzed using thematic analysis. The findings indicate that readiness is a multidimensional construct shaped by four interrelated dimensions: governance and strategic commitment, organizational capability configuration, ecosystem and market responsiveness, and structural–infrastructural readiness. Governance flexibility and leadership commitment determine strategic direction, while capability configuration reflects the institution’s ability to integrate resources and knowledge. External alignment is captured through industry engagement and market responsiveness, and sustained implementation depends on adequate infrastructure and administrative systems. This study contributes by advancing organizational readiness beyond traditional psychological perspectives toward a systemic capability-alignment framework tailored to executive education development. The proposed framework offers a structured approach for institutional leaders to assess preparedness, align internal capabilities with external expectations, and manage transformation more effectively